Given two vectors, \( \mathbf{a} = \mathbf{i} + 2\mathbf{j} - 3\mathbf{k} \) and \( \mathbf{b} = 2\mathbf{i} - 3\mathbf{j} - 5\mathbf{k} \).
Step 1: Calculate \( \mathbf{a} - \mathbf{b} \)
\[
\mathbf{a} - \mathbf{b} = (\mathbf{i} + 2\mathbf{j} - 3\mathbf{k}) - (2\mathbf{i} - 3\mathbf{j} - 5\mathbf{k}).
\]
Simplifying this expression:
\[
\mathbf{a} - \mathbf{b} = -\mathbf{i} + 5\mathbf{j} + 2\mathbf{k}.
\]
Step 2: Find the magnitude of \( \mathbf{a} - \mathbf{b} \)
The magnitude is given by:
\[
|\mathbf{a} - \mathbf{b}| = \sqrt{(-1)^2 + 5^2 + 2^2}.
\]
Simplifying further:
\[
|\mathbf{a} - \mathbf{b}| = \sqrt{1 + 25 + 4} = \sqrt{30}.
\]
Step 3: Calculate \( |\mathbf{a}| \) and \( |\mathbf{b}| \)
For \( |\mathbf{a}| \), we have:
\[
|\mathbf{a}| = \sqrt{1^2 + 2^2 + (-3)^2} = \sqrt{1 + 4 + 9} = \sqrt{14}.
\]
For \( |\mathbf{b}| \), we compute:
\[
|\mathbf{b}| = \sqrt{2^2 + (-3)^2 + (-5)^2} = \sqrt{4 + 9 + 25} = \sqrt{38}.
\]
Step 4: Verify the relationship between the magnitudes
Now, we compare \( |\mathbf{a} - \mathbf{b}| \) with \( |\mathbf{b}| - |\mathbf{a}| \):
\[
|\mathbf{b}| - |\mathbf{a}| = \sqrt{38} - \sqrt{14}.
\]
Since we know that \( |\mathbf{a} - \mathbf{b}| = \sqrt{30} \), and \( \sqrt{30}>\sqrt{38} - \sqrt{14} \), the inequality holds true:
\[
|\mathbf{a} - \mathbf{b}|>|\mathbf{b}| - |\mathbf{a}|.
\]
Final Answer:
\[
\boxed{|\mathbf{a} - \mathbf{b}|>|\mathbf{b}| - |\mathbf{a}|}
\]